The effect of curcumin on lipid peroxidation and selected antioxidants in irradiated rats - Ozcelik, Mehtap; Erisir, Mine; Guler, Osman; Baykara, Murat; Kirman, Esra (Veterinarni A Farmaceuticka Univerzita Brno, 2018)
The effect of irradiation on oxidants and antioxidants in selected tissues and a possible protective effect of curcumin on these indices were investigated. A total of 28 rats were divided into 3 groups; group 1 was control; group 2 was the irradiation group, saline was administered intraperiotenally (i.p.) for three days and then, 9 Gy gamma irradiation was applied; group 3 was the irradiation + curcumin group: curcumin was given i.p. for three days at 200 mg/kg body weight and then the same dose of irradiation was applied. A significant increase in malondialdehyde (MDA) was detected in the liver, kidney, and brain tissues of the rats as a result of irradiation (P < 0.01). Glutathione peroxidase (GSH-Px) activity in all the tissues (except for kidneys) decreased (P < 0.01), liver SOD (superoxide dismutase) activity decreased (P < 0.05), and GSH (glutathione) levels in kidney and ovary tissues (P < 0.001) significantly increased. While curcumin administration returned the increased MDA levels in the kidneys and brain in result of irradiation to normal (P < 0.01), it did not return the increased MDA levels in the liver tissue to normal (P < 0.001) despite significantly reducing them. While decreased GSH-Px and SOD activity in the liver in result of irradiation increased with the addition of curcumin (P < 0.05), increased GSH levels in the kidneys and ovaries returned to control levels (P < 0.001). When MDA values were examined, it was found that the addition of curcumin protected the liver, kidneys and brain from the oxidative damage caused by irradiation.
Keywords: Gamma-ray; phenolic compound; oxidative stress